2000
DOI: 10.1046/j.1365-2656.2000.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of food and predators on reproduction and overwinter survival of arctic ground squirrels

Abstract: Summary1. We examined the eects of food and predators on population limitation in the arctic ground squirrel (Spermophilus parryii plesius Richardson) in the boreal forest of the south-western Yukon. We focused on ground squirrel reproduction and overwinter survival. 2. Squirrel populations were monitored by live-trapping and radio-telemetry from 1993 to the spring of 1996 on four control and four experimental areas (one predator exclosure treatment, two food addition treatments, and one predator exclosure plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 64 publications
8
111
4
Order By: Relevance
“…For prey species, densities were sampled from sites throughout the valley (Folkard and Smith 1995;Karels and were assessed in a 100 km 2 intensive study area, and these densities were extrapolated to the entire area Smith 1994, 2001;Rohner 1996;Rohner and others 2001). For the mammalian predators, density estimates were made on a valleywide basis-that is, 400 km 2 (O'Donoghue andothers 1997, 2001).…”
Section: Study Systemmentioning
confidence: 99%
“…For prey species, densities were sampled from sites throughout the valley (Folkard and Smith 1995;Karels and were assessed in a 100 km 2 intensive study area, and these densities were extrapolated to the entire area Smith 1994, 2001;Rohner 1996;Rohner and others 2001). For the mammalian predators, density estimates were made on a valleywide basis-that is, 400 km 2 (O'Donoghue andothers 1997, 2001).…”
Section: Study Systemmentioning
confidence: 99%
“…Spring population estimates were used to calculate rates of change. We then used a multiple regression to evaluate the importance of various demographic parameters (per capita reproductive output and overwinter survival, both from Karels et al (2000), and adult and juvenile survival during the active season) on rates of population change during our study. Changes in avian-and mammalian-predator numbers (calculated in autumn of each year) and snowshoe hare autumn population densities were also monitored from 1990 to 1995.…”
Section: Population Trends In Arctic Ground Squirrels Snowshoe Haresmentioning
confidence: 99%
“…Hubbs and Boonstra (1997) examined the effects of predation and food on arctic ground squirrel populations during the early decline phase of the snowshoe hare cycle; among-treatment effects indicated that food was the major factor limiting ground squirrel populations, whereas among-year effects clearly indicated that predation must have accounted for major differences in adult survival during this time. Karels et al (2000) found that food supplementation increased adult and juvenile growth rates, body condition, and reproduction, and possibly interacted with predation to affect population densities of arctic ground squirrels in the low phase of the snowshoe hare cycle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in desert ecosystems, relying solely on photoperiod to anticipate habitat and ecological changes can certainly endanger reproduction and offspring success, as these harsh environments are generally characterized by unpredictable climatic conditions and food and water availability (Noy-Meir, 1973;Bronson, 1985;Bronson, 2009). Several environmental cues have been suggested to interact with photoperiod to form a more reliable network to prime the timing of reproduction in unpredictable environments, including precipitation, food availability and temperature (Bronson and Heideman, 1994;El-Bakry et al, 1998;Karels et al, 2000;Shanas and Haim, 2004).…”
Section: Introductionmentioning
confidence: 99%